A 3D bi-functional porous N-doped carbon microtube sponge electrocatalyst for oxygen reduction and oxygen evolution reactions. Issue 10 (2nd September 2016) - Li, Jin-Cheng; Hou, Peng-Xiang; Zhao, Shi-Yong; Liu, Chang; Tang, Dai-Ming; Cheng, Min; Zhang, Feng; Cheng, Hui-Ming
Abstract : A flexible, dictyophora-like sponge of porous N-doped carbon microtubes demonstrates excellent electrocatalytic activities for both the oxygen reduction reaction and oxygen evolution reaction. Abstract : A flexible, large-area three-dimensional porous N-doped carbon microtube (NCMT) sponge was prepared via a simple and low-cost process of pyrolyzing facial cotton. Due to its unique structure with a micron-scale hollow core and well-graphitized and interconnected porous walls, the NCMT sponge exhibits incomparable electrocatalytic activity for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) with a small potential difference of 0.63 V between the OER current density at 10 mA cm −2 and the ORR current density at −3 mA cm −2, which is the best to date.